Association of different kinds of obesity with diabetic retinopathy in patients with type 2 diabetes - Xiaoling Liang; Wei Wang; Ling Jin; Wenyong Huang; Wangting Li; Lanhua Wang; Xia Gong; Jie Meng; Yuting Li; Kun Xiong (BMJ Open)
Introduction Although obesity is one of the established risk factors of diabetes mellitus, the relationship between obesity and diabetic retinopathy (DR) remains unclear in different studies. This study aimed to investigate the association of DR with four obesity-related indexes, including body mass index (BMI), waist to hip ratio (WHR), waist to height ratio (WHtR) and body adiposity index (BAI) in patients with diabetes.Research design and methods We prospectively enrolled 2305 patients with diabetes (2305 eyes) in the Guangzhou Diabetic Eye Study between November 2017 and December 2019 to investigate the prevalence and the association of different types of obesity with DR using BMI, WHR, WHtR and BAI. DR, diabetic macular oedema (DME) and vision-threatening DR (VTDR) were selected as primary outcomes. BMI was categorised as normal (18.5–22.9 kg/m2), overweight (23.0–25.0 kg/m2) and obese (>25.0 kg/m2); WHR, WHtR and BAI were categorised into quarters.Results A total of 336 (14.58%), 93 (4.03%) and 98 (4.25%) developed DR, DME and VTDR, respectively. The prevalence of DR, DME and VTDR was higher in patients with higher BMI/WHR or lower WHtR/BAI. In the univariate regression model, WHR correlated positively with DR, while WHtR and BAI correlated negatively with DR, DME and VTDR. The association remained independent of age, sex and lipid metabolism parameters. In the multivariate model, obese presented as a protective factor for DME and VTDR, while the second quarter of WHtR(Q2-WHtR) presented as a risk factor.Conclusions As high as 67.8% of patients with diabetes were overweight or obese. Obese presented as a significant protective factor of VTDR, while Q2-WHtR presented as a significant risk factor. Therefore, more attention should be paid to centripetal obesity as well as general obesity. Further research is also needed to focus on the improvement of sex-specific weight management in patients with diabetes.